Left Atrial Function in Young Patients With Cryptogenic Stroke and Patent Foramen Ovale: A Left Atrial Longitudinal Strain Study - Gazagnes, Julie; Gollion, Cédric; Fournier, Pauline; Cariou, Eve; Larrue, Vincent; Lairez, Olivier (Frontiers in Neurology, 2020)
Background: The study of left atrial (LA) longitudinal strain by speckle tracking is a reliable method for analyzing LA function that could provide relevant information in young patients with cryptogenic stroke (CS). The aim of this study was to investigate whether the presence of a patent foramen ovale (PFO) impacts the LA longitudinal strain in a population of young patients with first CS. Methods and Results: Patients aged 18 to 54 years, treated consecutively in a university hospital for first CS, were included in this study. The presence of a PFO and an atrial septal aneurysm (ASA) was investigated using transesophageal echocardiography and transcranial Doppler. Speckle tracking analysis was performed on transthoracic echocardiography, allowing the measurement of global, passive, and active longitudinal LA strain, corresponding to the reservoir, conduit, and contractile function, respectively. A total of 51 patients were included in the study. In a multivariable analysis, overweight was associated with reduced global and passive LA longitudinal strain (P = 0.013 and P = 0.018, respectively), and hypertension was associated with reduced active LA longitudinal strain (P = 0.049). LA longitudinal strain was not different between patients with PFO or PFO plus ASA and patients without PFO. Conclusion: LA longitudinal strain in young subjects with CS was impaired in the presence of overweight and hypertension, but not of PFO or PFO plus ASA.